2020
DOI: 10.1021/acs.langmuir.9b03251
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Serum Albumin Enhances Silver Nanoparticle Dissolution Kinetics in a Size- and Concentration-Dependent Manner

Abstract: The dissolution of silver nanoparticles (AgNPs) to release Ag(I)(aq) is an important mechanism in potentiating AgNP cytotoxicity and imparting their antibacterial properties. However, AgNPs can undergo other simultaneous biophysicochemical transformations, such as protein adsorption, which can mediate AgNP dissolution behaviors. We report the comprehensive analysis of AgNP dissolution and protein adsorption behaviors with monolayer surface coverage of AgNPs by bovine serum albumin (BSA). AgNP dissolution rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 63 publications
4
34
0
1
Order By: Relevance
“…However, NP surface-coated species are usually surface-active molecules with dual affinity to interact simultaneously with the liquid and solid phases; , therefore, they are prone to undergo hydrophilic and hydrophobic interactions. Such interactions significantly depend on several solution properties such as concentration, temperature, ionic strength, and so forth. Concentration is the most important factor in view of the load-carrying ability of NPs for a specific application. Thus, high concentration of NPs makes them easily vulnerable for NP–NP interactions, , which are usually the manifestation of both hydrophilic and hydrophobic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…However, NP surface-coated species are usually surface-active molecules with dual affinity to interact simultaneously with the liquid and solid phases; , therefore, they are prone to undergo hydrophilic and hydrophobic interactions. Such interactions significantly depend on several solution properties such as concentration, temperature, ionic strength, and so forth. Concentration is the most important factor in view of the load-carrying ability of NPs for a specific application. Thus, high concentration of NPs makes them easily vulnerable for NP–NP interactions, , which are usually the manifestation of both hydrophilic and hydrophobic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption constants obtained by two complementary approaches yielded similar results, with slightly lower standard deviations for the LSPR method. A previously published work of Boehmler et al 32 on the interactions between BSA and AgNPs using the LSPR method showed that adsorption constants increased with NP diameter. Contrarily, Dennison et al 41 obtained a higher adsorption constant for BSA onto the AuNP surface compared to our results, even though they used smaller AuNPs.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…, aggregation) or changes of the immediate environment (due to ligand adsorption). Tracking the spectral changes following the exposure of NPs (either immobilized on a chip or free in solution) to the analyte of interest is the basis of the LSPR method in biosensing. The technique can be used to monitor parameters of the nano–bio interaction such as protein binding kinetics on nanosurfaces. The LSPR technique is a sensitive, label-free, simple, and cheap technique that offers detection, quantification, and/or binding characterization of different analytes without the need for sample purification. ,, Nevertheless, the use of LSPR for determining NPs–protein binding affinity and kinetics has still not been widely applied.…”
Section: Introductionmentioning
confidence: 99%
“…43−45 Also, proteins may adsorb Ag(I) and dissolve the AgNPs. 32,46 Additionally, it has been widely reported that the AgNP−protein interaction leads to the "protein corona" formation around the AgNPs. 47 Protein corona induces changes in the AgNPs' traits, such as size, stability, and even in the way they interact with cells.…”
Section: Resultsmentioning
confidence: 99%